The Bad Taste of Medicines: Overview of Basic Research on Bitter Taste - Mennella, Julie A. (2013)
BACKGROUND: Many active pharmaceutical ingredients taste bitter and thus are aversive to children, as well as many adults. Encapsulation of the medicine in pill or tablet form, an effective method for adults to avoid the unpleasant taste, is problematic for children. Many children cannot or will not swallow solid dosage forms. OBJECTIVE: This review highlights basic principles of gustatory function, with a special focus on the science of bitter taste, derived from studies of animal models and human psychophysics. We focus on the set of genes that encode the proteins that function as bitter receptors, as well as the cascade of events that lead to multidimensional aspects of taste function, highlighting the role that animal models played in these discoveries. We also summarize psychophysical approaches to studying bitter taste in adult and pediatric populations, highlighting evidence of the similarities and differences in bitter taste perception and acceptance between adults and children and drawing on useful strategies from animal models. RESULTS: Medicine often tastes bitter, and because children are more bitter sensitive than are adults, this creates problems with compliance. Bitter arises from stimulating receptors in taste receptor cells, with signals processed in the taste bud and relayed to the brain. However, there are many gaps in our understanding of how best to measure bitterness and how to ameliorate it, including whether it is more efficiently addressed at the level of receptor and sensory signaling, at the level of central processing, or by masking techniques. All methods of measuring responsiveness to bitter ligands—in animal models, through human psychophysics, or with “electronic tongues”—have limitations. CONCLUSIONS: Better-tasting medications may enhance pediatric adherence to drug therapy. Sugars, acids, salt, and other substances reduce perceived bitterness of several pharmaceuticals, and although pleasant flavorings may help children consume some medicines, they often are not effective in suppressing bitter tastes. Further development of psychophysical tools for children will help us better understand their sensory worlds. Multiple testing strategies will help us refine methods to assess acceptance and compliance/adherence by various pediatric populations. Research involving animal models, in which the gustatory system can be more invasively manipulated, can elucidate mechanisms, ultimately providing potential targets. These approaches, combined with new technologies and guided by findings from clinical studies, will potentially lead to effective ways to enhance drug acceptance and compliance in pediatric populations.